Determinants of Firm Growth: The Case of Sachet Water Firms in Minna, Nigeria - Baba Isah Usman; Umaru Mustapha Zubairu; Dauda Abdulwaheed; Ibrahim Sojeko; Bilkisu Mohammed Ovosi; Ekanem Ediuku (LPPM of NAROTAMA UNIVERSITY, 2020)
Purpose: The objective of this study was to analyze the influence of Entrepreneurial Infrastructure (EI) on the profitability of Sachet Water Firms (SWFs) in Minna. Design/methodology/approach: This was done through the use of personal interviews for the collection of qualitative data from owners/managers of SWFs. The population of the study included all the 165 SWFs in Minna and the sample size was 10 which was determined by interview saturation point. Thematic analysis was used in analyzing the transcribed audio recordings of the interviews conducted. Findings: Findings revealed that there is an EI deficit in Minna, which has led to increased expenses on the provision of alternative EI by SWFs and has increased their operational costs thereby reducing their profitability. Research limitations/implications: Firstly, with thirty-six states in Nigeria, the findings of this study, covering the Capital of only one of the States (Niger) cannot be generalized for the entire country, rather it must be taken within the context of the region covered. Secondly, only one industry out of many that make up the Nigerian economy is selected for investigation. Thirdly, the researcher was faced with the negative attitude of some respondents who were not willing to participate in the research or provide the needed data for analysis. Lastly, not all the SWFs in Minna were included in the study, only those that have operated for up to three years were included. Future studies can bridge these research gaps by carrying out research in other parts of Nigeria on the same subject matter. Practical implications: Findings of this study would be of help to the existing SMEs in Nigeria, particularly the SWFs in further understanding the complexities of the infrastructural challenges militating against their growth and how to overcome them. Originality/value: This study contributes to the body of knowledge on the nexus between EI and the general performance of SMEs. Paper type: Research paper.